Unveiling Tourist Behaviour in Time of Smart Tourism Technology and Social Influence - Alnasser, Emad Mohammed; Alkhozaim, Sultan Mohammed (Transformations In Business & Economics, 2024)
This research aims to explore the existing relationship between perceived smart tourism technology and self-congruity with travel experience satisfaction and tourist temporal revisit intention. Moreover, this research used travel experience satisfaction as a mediating variable and electronic word-of-mouth as a moderating variable among the relationship of perceived smart tourism technology, self-congruity, and tourist temporal revisit intention. This research collected data from 264 tourists across various tourist sites in Saudi Arabia. To achieve the aim of this research, this study has employed the STATA software with SEM (structural equation modelling) approach. The findings of this research have shown a significant association between direct relationships between perceived smart tourism technology and self-congruity with tourist temporal revisit intention. Moreover, findings also confirmed that the relationship between perceived smart tourism technology, self-congruity, and tourist temporal revisit intention is also moderated by electronic word-of-mouth and mediated by travel experience satisfaction. This research contributes to the advancement of tourism and technology utilisation-related theories. Destination managers and marketers can use smart tourism technologies, build visitor loyalty, and maximis e-tourist satisfaction to boost competitiveness and experience. Electronic word-of-mouth influences tourists’ views and intents, according to this study. It emphasis the necessity for locations to engage passengers on social media and digital platforms.